Digital Scholarly Editing Theories and Practices - Driscoll, Matthew James; Pierazzo, Elena (Digital Humanities Series, 2016)
This volume presents the state of the art in digital scholarly editing. Drawing together the work of established and emerging researchers, it gives pause at a crucial moment in the history of technology in order to offer a sustained reflection on the practices involved in producing, editing and reading digital scholarly editions-and the theories that underpin them. The unrelenting progress of computer technology has changed the nature of textual scholarship at the most fundamental level: the way editors and scholars work, the tools they use to do such work and the research questions they attempt to answer have all been affected. Each of the essays in Digital Scholarly Editing approaches these changes with a different methodological consideration in mind. Together, they make a compelling case for re-evaluating the foundation of the discipline-one that tests its assertions against manuscripts and printed works from across literary history, and the globe. The sheer breadth of Digital Scholarly Editing, along with its successful integration of theory and practice, help redefine a rapidly-changing field, as its firm grounding and future-looking ambit ensure the work will be an indispensable starting point for further scholarship. This collection is essential reading for editors, scholars, students and readers who are invested in the future of textual scholarship and the digital humanities.